Increasing the efficiency of electricity use by residential and public buildings in the presence of hybrid solar power plants in the electricity market - Lytvyn, V. (Energy and Automation, 2025)
The article is devoted to the analysis of electricity consumption schedules of public and residential buildings and the operation and optimization of the operation of rooftop hybrid solar power plants. The wide distribution of hybrid solar inverters, due to both the desire to reduce energy consumption costs and the need to provide backup power to critical consumers, created prerequisites for using the advantages of the electricity market. Storage and the possibility of interchangeability of energy sources (for example, district heating and electricity supply for heating and hot water supply) allows us to talk about buildings in the context of "active consumers". The developed standard schedules of electricity consumption by buildings allow optimizing the use of their own solar power plant to minimize the cost of electricity supply, taking into account the possibility of storage systems and the possibility of using surplus solar generation for heating, air conditioning and hot water supply. The simulation of the solar power plant operating modes in the following options: "consumption for own needs without optimizing the use of storage systems", "sale of surplus electricity on the market", "consumption for own needs with optimization of storage systems" indicates the possibility of reducing the cost of energy consumption of the facility by 30-40% depending on the daily solar insolation. The use of the model allows you to configure the operating modes of hybrid inverters to optimize energy consumption. It is advisable to focus further research on the creation of an alternative control system for inverters with optimization depending on the load profile of the building.Key words: hybrid power supply, energy consumption modeling, cost optimization, demand side